OEDGE modeling of far-SOL tungsten impurity sources and screening in WEST. (October 2022) - Maeker, J.B.; Nichols, J.H.; Donovan, D.C.; Grosjean, A.; Gunn, J.; Fedorczak, N.; Guillemaut, C.; Klepper, C.C.; Unterberg, E.A.; Easley, D.C.; Team, WEST
Abstract: The plasma background and impurity transport in the scrape-off layer (SOL) of the WEST tokamak are modeled for three discharges over a Psep power scan ranging between 1.5 and 2.35 MW. An extended modeling grid is used to investigate far-SOL sourcing from the WEST baffle and lower divertor. Divertor Langmuir probe data at the targets and upstream data from reciprocating Langmuir probes and interferometry/reflectometry is used to create a simulated background plasma with the OSM and EIRENE codes. W-I spectroscopic data from WEST at the lower divertor and baffle is used to estimate the sputtered W flux as an input to the impurity transport code DIVIMP. A potential mechanism for far-SOL impurities from the baffle to transport into the near-SOL is proposed and discussed in terms of the model's force balances. Analysis of simulated impurity transport showed similar impurity density at the separatrix for the mid and high-power cases despite the high-power case having 10% more sputtered W. This is explained by the combination of differing trends in the sourcing and screening with scaling power.